Hepatic Localization of Macrophage Phenotypes during Fibrogenesis and Resolution of Fibrosis in Mice and Humans - Beljaars, Leonie; Schippers, Marlies; Reker-Smit, Catharina; Martinez, Fernando O.; Helming, Laura; Poelstra, Klaas; Melgert, Barbro N. (Frontiers in Immunology, 2014)
Macrophages have been found to both promote liver fibrosis and contribute to its resolution by acquiring different phenotypes based on signals from the micro-environment. The best-characterized phenotypes in the macrophage spectrum are labeled M1 (classically activated) and M2 (alternatively activated). Until now the in situ localization of these phenotypes in diseased livers is poorly described. In this study, we therefore aimed to localize and quantify M1- and M2-dominant macrophages in diseased mouse and human livers. The scarred collagen-rich areas in cirrhotic human livers and in CCl4-damaged mouse livers contained many macrophages. Though total numbers of macrophages were higher in fibrotic livers, the number of parenchymal CD68-positive macrophages was significantly lower as compared to normal. Scar-associated macrophages were further characterized as either M1-dominant (IRF5 and IL-12) or M2-dominant (CD206, TGM2 and YM-1) and significantly higher numbers of both of these were detected in diseased livers as compared to healthy human and mouse livers. Interestingly, in mouse livers undergoing resolution of fibrosis, the total number of CD68+ macrophages was significantly lower compared to their fibrotic counterparts. M2-dominant (YM-1) macrophages were almost completely gone in livers undergoing resolution, while numbers of M1-dominant (IRF5) macrophages were unchanged and the proteolytic activity (MMP9) increased. In conclusion, this study shows the distribution of macrophage subsets in livers of both human and murine origin. The presence of M1-and M2-dominant macrophages side by side in fibrotic lesions suggests that both are involved in fibrotic responses, while the persistence of M1-dominant macrophages during resolution may indicate their importance in regression of fibrosis. This study emphasizes that immunohistochemical detection of M1/M2-dominant macrophages provides valuable information in addition to widely used flow cytometry and gene analysis.